Constructing the narrative of the sustainability fix: Sustainability, social justice and representation in Austin, TX. (January 2016) - Long, Joshua
In recent years Austin, Texas has gained popular recognition as a 'sustainable city' while experiencing robust economic growth. Austin's ability to resolve many of the political tensions between development and environmental protection have made it a favoured case study for North American policymakers who seek to mimic the 'Austin model'. However, despite recognised environmental achievements, the popular storyline of Austin's move toward sustainability overlooks key aspects of sustainable development, including equitable political representation, affordability, displacement of vulnerable populations and other social justice issues. Using While et al.'s 'sustainability fix' as a conceptual framework, this paper explores the historical development, ideological construction and strategic implementation of Austin's sustainability agenda. In doing so, this paper moves beyond a lateral understanding of sustainability rhetoric toward a more nuanced and critical analysis of the selective promotion and implementation of sustainability agendas, as well as the consequences they have for social justice and equity in the 'sustainable cities' of the 21st century.